Advances in the human side of service engineering : proceedings of the AHFE 2016 International Conference on The Human Side of Service Engineering, July 27-31, 2016, Walt Disney World®, Florida, USA /: proceedings of the AHFE 2016 International Conference on The Human Side of Service Engineering, July 27-31, 2016, Walt Disney World®, Florida, USA. ([2016]) - Unknown
No abstract available